(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the transformative impact of second language acquisition in today’s globalized world, with a particular focus on English as a global lingua franca. It synthesizes recent research and theoretical perspectives to highlight how language learning enhances intercultural communication, career development, and cognitive functioning. Drawing on the works of Kramsch, Gardner, Bialystok, and others, the paper emphasizes the multifaceted benefits of multilingualism, including increased social integration, professional opportunities, and improved executive functions. The article argues that language learning is not merely an academic pursuit but a lifelong investment in personal growth, societal inclusion, and mental agility. It calls for broader support of language education by individuals, institutions, and policymakers.